Hybric solar battery charger for how power application - Arina Amira binti Abdul Aziz (Department of Electronic Engineering Technology, Faculty of Engineering Technology, University Malaysia Perlis, 2015)
Nowadays, the used of battery in electric and electronic appliances are widely used especially, for outdoor activities. The travellers will use electronic devices such as MP3 and digital cameras that require batteries as well. However, at one point, the battery will be depleted powers. This is because the life span of the battery is not as promising due to the degrading of its life span. Based on studies that have been made by a few of scientists, there is an alternative that can simplify and solve these problems which is hybrid battery charger. Hybrid is something turned on by more than one power source. In addition, advances in renewable energy technology have made us not be too dependent on one energy source only. In this project, the hybrid solar battery charger circuits of rechargeable triple A battery as supply and solar panel as alternative source. For the alternative source, solar energy is one of the renewable energy and this energy is provided by the sun. The production of solar electricity is made from the form of solar radiation. Electricity is produces directly from photovoltaic, PV and cells. In this project, it is desirable to extract maximum power from solar cells under sunlight isolation conditions. A hybrid solar battery with better efficiency and improve life span are expected. Thus, the results are verified by Proteus ISIS 7 Professional software and hardware results to prove the switching between the solar and battery in this project.